Safety and efficacy of the feed additives l‐histidine and l‐histidine monohydrochloride monohydrate produced with Corynebacterium glutamicum KCCM 80389 for all animal species (CJ Europe GmbH) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Roberto Edoardo Villa; Giovanna Azimonti; Eleftherios Bonos; Henrik Christensen; Mojca Durjava; Birgit Dusemund; Ronette Gehring; Boet Glandorf; Maryline Kouba; Marta López‐Alonso; Francesca Marcon; et al. (EFSA Journal, 2025)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of l‐histidine and l‐histidine monohydrochloride monohydrate produced with a genetically modified strain of Corynebacterium glutamicum (KCCM 80389) as nutritional and sensory feed additives for all animal species and categories. l‐Histidine and l‐histidine monohydrochloride monohydrate manufactured by fermentation with C. glutamicum KCCM 80389 do not give rise to any safety concern regarding the genetic modifications of the production strain. No viable cells or DNA of the production strain were detected in the final products. The FEEDAP Panel concluded that the use of l‐histidine and l‐histidine monohydrochloride monohydrate produced with C. glutamicum KCCM 80389 in feed raises no safety concerns for the target species when supplemented in appropriate amounts to the diet according to the nutritional needs of the species. The FEEDAP Panel had concerns on the use of l‐histidine and l‐histidine monohydrochloride monohydrate in water for drinking. The FEEDAP Panel concluded that the use of l‐histidine and l‐histidine monohydrochloride monohydrate produced by fermentation with C. glutamicum KCCM 80389 in animal nutrition are safe for the consumers of products from animals receiving the additive, and to the environment. Regarding the user safety, the additives are not considered irritant to skin or eyes and are not considered potential skin sensitisers. The additives were regarded as effective sources of the amino acid l‐histidine for all non‐ruminant species. To be as efficacious in ruminants as in non‐ruminants, it should be protected from ruminal degradation.